Sosialisasi Microteaching sebagai Upaya Meningkatkan Keterampilan Mengajar Kreatif di MI Cikaso - Husnul; Aidah, Siti; Hilman, Cecep (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2024)
This community service activity aims to enhance the effectiveness of creative and quality teaching at MI Cikaso through the socialization of microteaching. The background of this activity is based on the need for teachers to develop more innovative teaching methods that align with technological advancements and curriculum demands. The method used in this activity is Participatory Action Research (PAR), which actively involves MI Cikaso teachers in all stages of the research, from planning, implementation, to evaluation. This activity includes microteaching training sessions, group discussions, and reflections that are expected to improve teachers' pedagogical competence and professionalism. The results of this activity indicate a significant improvement in teachers' ability to design and implement more interactive, student-centered learning. The conclusion of this activity is that the socialization of microteaching through the PAR approach is effective in enhancing the quality of teaching at MI Cikaso, as well as strengthening collaboration among teachers in creating a more dynamic and creative learning environment.